Pregnancy Outcome Following Maternal Exposure to Mirtazapine. Issue 3 (June 2015) - Winterfeld, Ursula; Klinger, Gil; Panchaud, Alice; Stephens, Sally; Arnon, Judy; Malm, Heli; te Winkel, Bernke; Clementi, Maurizio; Pistelli, Alessandra; Maňáková, Eva; Eleftheriou, Georgios; Merlob, Paul; et al.
<x xml:space="preserve">Abstract</x> Abstract This multicenter, observational prospective cohort study addresses the risk associated with exposure to mirtazapine during pregnancy. Pregnancy outcomes after exposure to mirtazapine were compared with 2 matched control groups: (1) exposure to any selective serotonin reuptake inhibitor (SSRI, control subjects with a psychiatric condition) and (2) no exposure to medication known to be teratogenic or any antidepressant (general control subjects). Data were collected by members of the European Network of Teratology Information Services between 1995 and 2011. Observations from 357 exposed pregnancies were compared with 357 pregnancies from each control group. The rate of major birth defects between the mirtazapine and the SSRI group did not differ significantly (4.5% vs 4.2%; odds ratio [OR], 1.1; 95% confidence interval [95% CI], 0.5–2.3; P = 0.9). A trend toward a higher rate of birth defects in the mirtazapine group compared with general control subjects (4.5% vs 1.9%; OR, 2.4; 95% CI, 0.9–6.3; P = 0.08) reached statistical significance after exclusion of chromosomal or genetic anomalies (4.1% vs 1.3%; OR, 3.3; 95% CI, 1.04–10.3; P = 0.03), but this difference became again nonsignificant if cases of exposure not comprising the first trimester were excluded from the analysis (3.4% vs 1.9%; OR, 1.8; 95% CI, 0.6–5.0; P = 0.26). The crude miscarriage rate did not differ significantly between the mirtazapine, the SSRI, and the general control groups (12.1% vs 12.0% vs 9.3%; P = 0.44). However, a higher rate of elective pregnancy termination was observed in the mirtazapine group compared with SSRI and general control subjects (7.8% vs 3.4% vs 5.6%; P = 0.03). This study did not observe a statistically significant difference in the rate of major birth defects after first-trimester exposure between mirtazapine, SSRI-exposed, and nonexposed pregnancies. A marginally higher rate of birth defects was, however, observed in the mirtazapine and SSRI groups compared with the low rate of birth defects in our general control subjects. Overall pregnancy outcome after mirtazapine exposure was similar to that of the SSRI-exposed control group.